Near‐Field Investigation of Luminescent Hyperuniform Disordered Materials. Issue 8 (27th February 2022) - Granchi, Nicoletta; Spalding, Richard; Lodde, Matteo; Petruzzella, Maurangelo; Otten, Frank W.; Fiore, Andrea; Intonti, Francesca; Sapienza, Riccardo; Florescu, Marian; Gurioli, Massimo
Abstract: Disordered photonic nanostructures have attracted tremendous interest in the past three decades, not only due to the fascinating and complex physics of light transport in random media, but also for peculiar functionalities in a wealth of interesting applications. Recently, the interest in dielectric disordered systems has received new inputs by exploiting the role of long‐range correlation within scatterer configurations. Hyperuniform photonic materials, that share features of photonic crystals and random systems, constitute the archetype of systems where light transport can be tailored from diffusive transport to a regime dominated by light localization due to the presence of photonic band gap. Here, advantage is taken of the combination of the hyperuniform disordered (HuD) design in slab photonics, the use of embedded quantum dots for feeding the HuD resonances, and near‐field hyperspectral imaging with sub‐wavelength resolution in the optical range to explore the transition from localization to diffusive transport. It is shown, theoretically and experimentally, that photonic HuD systems support resonances ranging from strongly localized modes to extended modes. It is demonstrated that Anderson‐like modes with high Q/V are created, with small footprint, intrinsically reproducible and resilient to fabrication‐induced disorder, paving the way for a novel photonic platform for quantum applications. Abstract : In this work, the gap between breakthrough predictions and possible applications at telecom wavelengths of hyperuniform disordered (HuD) photonic systems is filled, by designing and nanofabricating the first optically active HuD structures with embedded quantum dots emitting in the optical range, and performing near‐field hyperspectral imaging of HuD systems.